(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Pre-term childbirth remains one of the most pressing problems of modern obstetrics, and this is about 11% of the world.Preterm labor is said to stop prematurely during the gestational period from the 22nd week to the 37th week of pregnancy.FPY , which occurs with a violation of the placenta process and leads to the underdevelopment of the placenta, is one of the causes of premature birth. Therefore, at present, it is very important to develop modern diagnostic methods and apply preventive measures, which will allow you to identify pathological changes in the fetoplacentar complex at the initial, pre-clinical stage of the disease.